2017
DOI: 10.1186/s13104-017-2402-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological findings, treatment response and predictors of long-term outcome in a cohort of lupus nephritis patients managed according to the Euro-lupus regime: a retrospective analysis in Sri Lanka

Abstract: BackgroundDespite the improvement in survival of patients with lupus nephritis (LN) globally, there is sparse data from Sri Lanka (SL). The current study aims to describe the clinicopathological findings, treatment response and predictors of long-term outcome of patients with WHO class III–IV LN in SL, managed according to the Euro-lupus regime.ResultsOf 72 patients, 64 were females. In half of them, LN was diagnosed within the 1st year of the illness. The most common presenting feature was sub-nephrotic prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…For a vignette about a 14-year-old girl with LN class IV, our survey found that 32% of pediatric rheumatologists would opt for EuroLupus dosing of CYC, vs only 6% of pediatric rheumatologists who were posed the same vignette in 2009. This change over time may be reflective of many factors, including more widespread adoption of EuroLupus dosing outside of Europe for the treatment of adult patients 8,10,11,15,16 as well as the encouraging follow-up outcomes from the Euro-Lupus Nephritis Trial (ELNT), which demonstrated similar renal outcomes between EuroLupus and NIH CYC dosing at 10 years. 17,18 These findings, in addition to pediatric providers acquiring positive experiences with the use of EuroLupus dosing for the treatment of LN in children and adolescents, have likely influenced practice.…”
Section: Discussionmentioning
confidence: 99%
“…For a vignette about a 14-year-old girl with LN class IV, our survey found that 32% of pediatric rheumatologists would opt for EuroLupus dosing of CYC, vs only 6% of pediatric rheumatologists who were posed the same vignette in 2009. This change over time may be reflective of many factors, including more widespread adoption of EuroLupus dosing outside of Europe for the treatment of adult patients 8,10,11,15,16 as well as the encouraging follow-up outcomes from the Euro-Lupus Nephritis Trial (ELNT), which demonstrated similar renal outcomes between EuroLupus and NIH CYC dosing at 10 years. 17,18 These findings, in addition to pediatric providers acquiring positive experiences with the use of EuroLupus dosing for the treatment of LN in children and adolescents, have likely influenced practice.…”
Section: Discussionmentioning
confidence: 99%
“…The answer is maybe, because several studies suggest that an early therapeutic response in LN predicts good long-term kidney outcomes. [6][7][8] In these retrospective studies, early responses included complete remissions, partial remissions, and declines in proteinuria of at least a 50% after 3-6 months of treatment. However, these studies did not compare the long-term outcomes of 6-and 12-month complete responders, and other studies have shown that a decline in proteinuria to about 800 mg/d after 12 months of therapy also predicts good long-term kidney health.…”
mentioning
confidence: 99%